Information technology capability, knowledge management capability, and organizational agility: The role of environmental factors. (28th January 2021) - Panda, Sukanya; Rath, Santanu Kumar
Abstract: This study precisely investigates the relationship of information technology (IT) and knowledge management (KM) capabilities with organizational agility along with the moderating influence of external environmental actors on this linkage. A matched-pair field survey was conducted and pretested structured questionnaires were administered to accumulate primary responses from 300 business and IT personnel working in various Indian financial groups. The research findings encompass first, IT and KM capabilities are enablers of organizational agility, while KM capability is more effective on agility. Second, a more diverse and less hostile environment is required for IT and KM capabilities to have more positive influence on agility, yet the moderating effects of environmental factors are found to be more on IT–agility linkage than on KM–agility relationship. These inferences provide several implications for the business and IT executives to concentrate on leveraging both IT and KM capabilities for generating augmented organizational agility.